The Role of Women in Islamic Propagation: A Case Study of Tablighi Jamaat’s Nyai of Pesantren Al-Fatah, East Java, Indonesia - Yon Machmudi; Putih Kusumah Ardhani (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2020)
This article studies the role of women of the Tablighi Jamaat, a transnational Islamic propagation movement, in the process of Islamic propagation (da’wah) in Indonesia. It aims to analyze the role played by female followers of Tablighi Jamaat in developing da’wah by focusing on the role of nyai (female family members of a religious leader of traditional Islamic learning institution [pesantren]) in developing masturah da’wah in Pesantren Al-Fatah and Temboro Village. This study uses a qualitative approach to understand how nyai of Pesantren Al-Fatah were involved in da’wah activities in Temboro. The required data were collected through observation and interviews. The findings show that like their spouses who were obliged to go for da’wah in the form of khuruj, female followers of Tablighi Jamaat of Pesantren Temboro were assigned to conduct da’wah through masturah, a form of Islamic propagation which was only targeted on, organized and attended by the women of Tablighi Jamaah in Temboro with strict rules such the obligation of wearing face veils for all participants. Nyai of Pesantren Al-Fatah initiated, led, and developed masturah so that Tablighi Jamaat has attracted more followers and religious students and Temboro has experienced significant changes in social, religious, and economic aspects.